Peroxisomal Proliferator-Activated Receptor β/δ Deficiency Induces Cognitive Alterations - Espinosa-Jiménez, Triana; Busquets, Oriol; Cano, Amanda; Sánchez-López, Elena; Verdaguer, Ester; Parcerisas, Antoni; Olloquequi, Jordi; Auladell, Carme; Folch, Jaume; Wahli, Walter; Vázquez-Carrera, Manuel; Camins, Antoni; et al. (Frontiers in Pharmacology, 2022)
PPAR/, the most PPAR abundant isotype in the central nervous system, is involved in microglial homeostasis and metabolism, whose disturbances have been demonstrated to play a key role in cognitive decline. Although PPAR/ function is well-stablished in metabolism, its contribution in neuronal and cognitive process is underexplored. Therefore, the aim of the study is to determine the role of PPAR/ in the neuropathological pathways involved in cognitive decline and as to whether a risk factor implicated in cognitive loss such as obesity modulates neuropathological markers. To carry out this study, 6-month-old male PPARβ/δ-null (PPARβ/δ-/-) and wildtype (WT) littermates with the same genetic background (C57BL/6X129/SV) were used. Animals were fed either with conventional chow (CT) or with a palmitic acid-enriched diet (HFD). Thus, four groups were defined: WT CT, WT HFD, PPARβ/δ-/- CT and PPARβ/δ-/- HFD. Our results showed a decrease in dendritic spine density and synaptic markers in PPARβ/δ-/- mice, which were corroborated in the novel object recognition test (NORT). Likewise, our study demonstrated that the lack of PPARβ/δ receptor enhances gliosis in the hippocampus, contributing to astrocyte and microglial activation and to the increase in neuroinflammatory biomarkers. Additionally, alterations in the hippocampal insulin receptor pathway were found. Interestingly, while some of the disturbances caused by the lack of PPARβ/δ were not affected by feeding the HFD, others were exacerbated or required the combination of both factors. Taken together, the loss of PPARβ/δ-/- affects neuronal and synaptic structure, contributing to cognitive dysfunction and, they also present this receptor as a possible new target for the treatment of cognitive decline.